Daniel Alcides Carrion (1857–1885) and a history of medical martyrdom. (November 2015) - Chatterjee, Pranab; Chandra, Shivika; Biswas, Tamoghna
Daniel Carrion, a sixth-year medical student, died while investigating the effects of self-inoculation of the causative organism of Oroya Fever and Bartonellosis and thereby contributed to understanding of the disease before the organisms had been identified.